Nickel Supported Parangtritis Beach Sand (PP) Catalyst for Hydrocracking of Palm and Malapari Oil into Biofuel - Muh. Siddik Ibrahim; Wega Trisunaryanti; Triyono Triyono (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Nickel supported Parangtritis beach sand (PP) catalyst for hydrocracking of palm and malapari oil into biofuel has been conducted. The impregnation process of Nickel (Ni) metal on PP was carried out through the dry impregnation method (blending) using a precursor salt of NiCl2.6H2O with variations of Ni metal as much as 10 and 15 wt% of PP which produced Ni(A) and Ni(B) catalysts. Each catalyst was tested for activity and selectivity through the hydrocracking process of oil into biofuel using a semi-batch system reactor at a temperature of 450 oC, a hydrogen gas flow rate of 20 mL/minute for 2 hours, and a weight ratio of 1:200 catalyst:feed (w/w). The results showed that the Ni(A)/PP catalyst had the highest activity and selectivity with the yield of liquid products and the total biofuel fraction (biohydrocarbons) obtained from hydrocracking of palm oil of 68.50 and 49.87 wt%, respectively. Ni(A)/PP catalyst has a total acidity, surface area, and crystal size of 0.051 mmol/g, 4.44 m2/g, 25.86 nm, respectively. The reusability test of the Ni(A)/PP catalyst in the hydrocracking process of palm oil into biofuel after the third use resulted in a liquid product and the total biofuel fraction obtained was 64.20 and 41.46 wt%, respectively. The yield of liquid product and the total fraction of biofuel (biohydrocarbon) in hydrocracking malapari oil were 66.10, 47.83 wt%, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).